(untitled) (Medical Forum Monthly, 2024)
Objective: To determine frequency of firearm fatalities in Larkana region. Study Design: Descriptive study. Place and Duration of Study: The study was conducted at causality and department of forensic medicine and toxicology Chandka Medical College @ SMBBMU Larkana from 1st June 2013 to 31st May 2015. Materials and Methods: Out of 1870 dead bodies brought for autopsy at causality Chandka Medical College Hospital Larkana and those 357 (19%) cases were selected in whom death occurred due to firearm as mentioned in police inquest report and autopsy record conducted, with the permission of authorities data was collected and analyzed and cause of death was determined by external and internal examination of body. Results: Autopsy record shows that among 357 cases males with 309 (87%) were dominated on females with 48 (13%) with Male/Female ratio of 6:1. The victim ages range from 11 years to 70 years and with location of injuries as 127 (35.57%) on Chest, 92 (25.77%) on Head & Neck, 59 (16.52%) on Abdomen, 38 (10.64%) on Head&Chest, chest & abdomen 31 (8.68%) and 10 (2.82%) on limbs and other parts, with manner of homicide in majority (78.15%) of cases Conclusion: The majority of victims were young males belonging to rural areas with rifled firearm injuries on Chest, and Head & Neck as a cause of death.